Communicating and Visualising Urban Planning in Cold War Berlin - Christoph Bernhardt; Kathrin Meissner (Urban Planning, 2020)
This article analyses the dynamics of communication, specifically with regard to the significance of visualisations in urban planning between the two competing political regimes of East and West Germany in divided Berlin (1945–1989). The article will demonstrate the ways in which planners on either side of the Iron Curtain were confronted with matters unique to their own political contexts and conditions for public communication, as well as how they faced similar challenges in fields of urban renewal and negotiating public participation. The post-war decades in Berlin were marked by strong planning dynamics: large-scale reconstruction after WWII and the `showcase character' of political confrontation and competition. In this context, new strategies of communicating urban planning to the public were developed, such as large-scale development plans, public exhibitions and cross-border media campaigns. Paradigmatic shifts during the mid-1970s generated new discourses about urban renewal and historic preservation. The new focus on small-scale planning in vivid and inhabited inner-city neighbourhoods made new forms of communication and public depiction necessary. In the context of social and political change as well as growing mediatisation, planning authorities utilised aspects of urban identity and civic participation to legitimise planning activities. The article traces two small-scale planning projects for neighbourhoods in East and West Berlin and investigates the interrelation of visual communication instruments in public discourses and planning procedures during the 1980s, a period that prominently featured the new strategy of comprehensive planning. Furthermore, the article highlights the key role of micro-scale changes in the management of urban renewal along both sides of the wall and the emergence of neighbourhood civil engagement and participation.
Keywords: 710; Berlin; civic participation; communication strategy; planning history; public negotiation; small-scale planning; urban renewal; visualising planning